2017
DOI: 10.1002/cne.24185
|View full text |Cite
|
Sign up to set email alerts
|

In vivo expression of Nurr1/Nr4a2a in developing retinal amacrine subtypes in zebrafish Tg(nr4a2a:eGFP) transgenics

Abstract: The Nuclear receptor subfamily 4 group A member 2 (Nr4a2) is crucial for the formation or maintenance of dopaminergic neurons in the central nervous system including the retina, where dopaminergic amacrine cells contribute to visual function. Little is known about which cells express Nr4a2 at which developmental stage. Furthermore, whether Nr4a2 functions in combination with other genes is poorly understood. Thus, we generated a novel transgenic to visualize Nr4a2 expression in vivo during zebrafish retinogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…The results of the PCR array indicated that several genes were affected by glyphosate exposure. Nr4a2 is a transcription factor that is highly expressed in the brain and is crucial for the formation or maintenance of dopaminergic neurons in the central nervous system (CNS) ( 55 ). Wnt7b , known to be involved in Wnt signaling, may affect early neural progenitor differentiation by regulating the expression of pro-neural transcription factors, including the T-domain transcription factors Tbr1 and Tbr2 ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the PCR array indicated that several genes were affected by glyphosate exposure. Nr4a2 is a transcription factor that is highly expressed in the brain and is crucial for the formation or maintenance of dopaminergic neurons in the central nervous system (CNS) ( 55 ). Wnt7b , known to be involved in Wnt signaling, may affect early neural progenitor differentiation by regulating the expression of pro-neural transcription factors, including the T-domain transcription factors Tbr1 and Tbr2 ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit anti‐ calretinin (1:1,000; polyclonal; AB5054; lot# 2903043; Millipore; )—according to the manufacturer, this antibody recognizes the 29‐kDa protein in mouse and rat tissues (Su et al., 2010; Yanpallewar et al., 2010). This highly conserved epitope has also been labeled in hamster (Lee et al., 2004), zebrafish (Goodings et al., 2017) and turtle (Parks et al., 2017). We observed labeling consistent with these previous reports.…”
Section: Methodsmentioning
confidence: 99%
“…These include Gdnf [65], Elavl2 [66], Itpr1, Elavl4, Khdrbs1 [67], Rasgef1b [67], and Tcf12 [68]. Some of them are also involved in the differentiation of retinal progenitor cells and in the development of the eye (Nurr1, Elavl2, Plxna2, Rasgef1b, Wnt4, Sox11), tissues in which miR-204/211 shows a relevant role [42,44,66,[69][70][71][72][73] In a precise time window during embryonic development, miR-204/211 holds Nurr1 and its downstream targets repressed, preventing an early DA maturation. Later, during mDAn development, once the precursors are at the right differentiative stage, miR-204/211 expression becomes no longer necessary, Nurr1 expression is "released", and the DA maturation can progress.…”
Section: Discussionmentioning
confidence: 99%